- 10

- 0

fig 1

Given:

e

e

Deduced

e

e

e

e

e

e

-1/2+i(3

where n is greater than or equal to 1 or n=a/b where a is greater than or equal to 1 and b is odd

1

∴

(-1/2+i(3/2))

However this is absurd and I

have no idea what's wrong

(sorry about the formating it was better in docs)

Given:

e

^{iΘ}= cosΘ + i sinΘ (radians)e

^{πi}=-1Deduced

e

^{2πi}=(-1)^{2}e

^{2πi}=1e

^{(2/3)πi}=1^{1/3}e

^{(2/3)iπ}=1e

^{(2/3)iπ}=cos(2i/3)+i sin(2i/3)e

^{(2/3)iπ}=-1/2+i(3/2)-1/2+i(3

^{1/2}/2)=1where n is greater than or equal to 1 or n=a/b where a is greater than or equal to 1 and b is odd

1

^{n}=1∴

(-1/2+i(3/2))

^{n}=1However this is absurd and I

have no idea what's wrong

(sorry about the formating it was better in docs)

#### Attachments

Last edited: